Feminsime Eksistensialis Pada Novel "Re Dan Perempuan Karya Maman Suherman - Ferdinand, Muhammad; Endang, Anis; Heriazwi, Martha (Jurnal Multidisiplin Dehasen (MUDE), 2025)
This study aims to analyse and describe the representation of existential feminism in Maman Suherman's novel Re: dan peRempuan. Existential feminism emphasises that women have equal rights in education, economics, politics, and social life. Women have the right to education without discrimination from their families or their communities. This study uses a qualitative method with Roland Barthes' semiotic approach to examine the plot and themes in the novel. Data collection techniques were carried out through documentation to identify aspects related to the theme of existentialism. Data analysis was carried out in three stages: identifying narrative structures, interpreting denotative and contextual meanings, and uncovering hidden mythology. The results of this study aim to provide a comprehensive understanding of existentialist feminism as represented in the novel Re: and peRempuan, particularly in depicting women's struggles to assert their existence and agency within a patriarchal order.